Phytoplasma Infection of Cranberries Benefits Non-vector Phytophagous Insects - Pradit, Nakorn; Mescher, Mark C.; Wang, Yifei; Vorsa, Nicholi; Rodriguez-Saona, Cesar (Frontiers in Ecology and Evolution, 2019)
Despite increasing knowledge about the impacts of pathogens on the interactions between plants and insect vectors, relatively little is known about their effects on other, non-vector, organisms. In cranberries, phytoplasma infection causes false blossom disease, which is transmitted by leafhoppers. We hypothesized that changes in plant chemistry induced by phytoplasma infection might affect the performance and feeding behavior not only of vectors but also of other phytophagous insects. To test this, we measured growth, survival, and the number of leaves damaged by larvae of three common non-vector herbivores: spotted fireworm (Choristoneura parallela Robinson), Sparganothis fruitworm (Sparganothis sulfureana Clemens), and gypsy moth (Lymantria dispar L.) on phytoplasma-infected and uninfected cranberries (Vaccinium macrocarpon Ait.). We also assessed the effects of phytoplasma infection on nutrients and phytochemistry related to defenses. In general, larvae of all three herbivore species grew 2–3 times bigger, and damaged 1.5–3.5 times more leaves, while feeding on infected vs. uninfected plants. Survival of Sparganothis fruitworm larvae was also ~1.5 times higher on infected plants, while spotted fireworm and gypsy moth larval survival was not affected. In a long-term (5-week) assay, gypsy moth larval survival and mass were enhanced when feeding on phytoplasma-infected leaves. Levels of important plant nutrients (e.g., N, P, K, Ca, S, Mn, Fe, B, Al, and Na) were higher in infected plants, while levels of defensive proanthocyanidins were reduced by 20–40% compared to uninfected plants. In contrast, levels of Mg were lower in infected plants, while concentrations of Cu, Zn, and defensive flavonols were not affected. Taken together, these findings suggest that phytoplasma infection enhances plant nutritional quality, while reducing plant defenses in cranberries. These effects, in turn, may explain the observed enhancement of non-vector herbivore performance, as well as the higher number of damaged leaves, on infected plants. Improved understanding of the ecology of pathogen-plant-herbivore interactions could aid efforts to enhance plant resistance and suppress disease transmission in agricultural settings.